Sharp U-Net: Depthwise convolutional network for biomedical image segmentation. (September 2021) - Zunair, Hasib; Ben Hamza, A.
Abstract: The U-Net architecture, built upon the fully convolutional network, has proven to be effective in biomedical image segmentation. However, U-Net applies skip connections to merge semantically different low- and high-level convolutional features, resulting in not only blurred feature maps, but also over- and under-segmented target regions. To address these limitations, we propose a simple, yet effective end-to-end depthwise encoder-decoder fully convolutional network architecture, called Sharp U-Net, for binary and multi-class biomedical image segmentation. The key rationale of Sharp U-Net is that instead of applying a plain skip connection, a depthwise convolution of the encoder feature map with a sharpening kernel filter is employed prior to merging the encoder and decoder features, thereby producing a sharpened intermediate feature map of the same size as the encoder map. Using this sharpening filter layer, we are able to not only fuse semantically less dissimilar features, but also to smooth out artifacts throughout the network layers during the early stages of training. Our extensive experiments on six datasets show that the proposed Sharp U-Net model consistently outperforms or matches the recent state-of-the-art baselines in both binary and multi-class segmentation tasks, while adding no extra learnable parameters. Furthermore, Sharp U-Net outperforms baselines that have more than three times the number of learnable parameters. Highlights: We introduce a novel Sharp U‐Net architecture by designing new connections between the encoder and decoder subnetworks using a depthwise convolution of the encoder feature maps with a sharpening spatial filter to address the semantic gap issue between the encoder and decoder features. We show that the Sharp U‐Net architecture can be scaled for improved performance, outperforming baselines that have three times the number of learnable parameters. We demonstrate through extensive experiments the ability of the proposed model to learn efficient representations for both binary and multi‐class segmentation tasks on a variety of medical images from different modalities.